Gecko adhesion based sea star crawler robot - Acharya, Sampada; Roberts, Peter; Rane, Tejas; Singhal, Raghav; Hong, Peize; Ranade, Viraj; Majidi, Carmel; Webster-Wood, Victoria; Reeja-Jayan, B. (Frontiers in Robotics and AI, 2023)
Over the years, efforts in bioinspired soft robotics have led to mobile systems that emulate features of natural animal locomotion. This includes combining mechanisms from multiple organisms to further improve movement. In this work, we seek to improve locomotion in soft, amphibious robots by combining two independent mechanisms: sea star locomotion gait and gecko adhesion. Specifically, we present a sea star-inspired robot with a gecko-inspired adhesive surface that is able to crawl on a variety of surfaces. It is composed of soft and stretchable elastomer and has five limbs that are powered with pneumatic actuation. The gecko-inspired adhesion provides additional grip on wet and dry surfaces, thus enabling the robot to climb on 25° slopes and hold on statically to 51° slopes.